Anak Rimba School Management Strategy for the Preservation of Local Wisdom in Sarolangun Regency: A Literature Review of the Development of Environment-Based Teaching Materials - Mulyadi, Mulyadi; Handoko, Yudo; Muspawi, Mohamhamad; Sastrawati, Eka; Vahlepi, Sahrizal; Soleh, Warissuddin (Journal La Edusci, 2025)
This paper focuses on discussing the school management philosophie of Sekolah Anak Rimba located in the Sarolangun Regency of Indonesia, the role of which was to preserve local wisdom through the development of educational materials based on nature. Based on a qualitative literature review basing on 28 peer-reviewed articles identified in the last 10 years in the areas of indigenous pedagogy, place-based knowledge systems, and ecological teaching, the research synthesizes some empirical evidence, and it dawns on us that both worlds should be combined to manage effectively in Indigenous environments, which means a combination of formal pedagogy experiences with cultural epistemologies and exposure to the natural world. Sekolah anak rimba is a good example of such integration by making its curriculum more sensitive towards knowledge in forests, and including the community stakeholders in structures of governance and as well as using experiential and ecology-basedm materials to teach. At the same time, the research identifies the structural barriers to the development of Özlig which include the lack of teacher preparation, a lack of alignment of the program with the national education policy, and a lack of support within the institution. Reframing educational management as an aspect of Indigenous schooling to be more than cultural resilience and ecological stewardship can be a strategic dimension, the study provides a unique angle of viewing Indigenous schooling in Indonesia. Findings are topically applicable in larger movements towards integrating formal education and the local cultural and environmental setting, especially on the margins, that live in the forests.